Relational incongruence in neurodiverse workgroups: Practices for cultivating autistic employee authenticity and belonging - Longmire, Natalie H.; Vogus, Timothy J.; Colella, Adrienne (Human Resource Management, 2025)
Although much research has sought to understand how employees come to align themselves with the social norms and routines of their workgroups, management theory has largely overlooked the possibility that such alignment might be fundamentally at odds with what it means to be autistic. Autism, which accounts for a large share of organizational neurodiversity, is associated with seeing and processing the world differently from the non‐autistic societal norm. In the workplace, autistic employees often experience barriers to inclusion, in large part due fundamental dissimilarities in how they interact with and connect to others. To identify the barriers to autistic employees' workgroup inclusion, we develop a multilevel framework centered around relational incongruence, or differences in patterns of interrelating across (autistic and non‐autistic) neurotypes. We propose that non‐autistic workgroup norms (e.g., for the use of imprecise language) exacerbate relational incongruence, which in turn hinders experiences of authenticity and belonging for the autistic workgroup member. Finally, we identify managerial practices (e.g., relational job crafting) that are likely to protect against the negative consequences of relational incongruence, by fostering workgroup climates of normalized variance in patterns of interrelating and shared understandings across neurotypes.